(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to evaluate the quality of development service in the Aga Khan Foundation for development from the perspective of teams that work in the foundation and, specifically by teams that concerned with the service delivery process. To achieve the objectives of the study, a special questionnaire was developed and distributed to a sample of 60 members of the working individuals in the Aga Khan Foundation for development in Hama, Salamiya city. For analyzing data and testing the hypotheses, many statistical have been used depending on the statistics program SPSS. Depending on that, the study identified that: The results showed that the degree level of quality evaluation of the development services in Aga Khan Foundation from the perspective of the teams that work in the foundation came with a high degree, which indicates a clear tendency for teams that work in the Aga Khan Foundation on the quality of development service that they provide . The study gives many recommendations to improve the quality of the provided development service through achieving the satisfaction of internal customers in the Foundation.